Heat Acclimation Enhances Brain Resilience to Acute Thermal Stress in Clarias fuscus by Modulating Cell Adhesion, Anti-Apoptotic Pathways, and Intracellular Degradation Mechanisms - Yingyi Guan; Cunyu Duan; Xinyu Xie; Zhuoying Luo; Dayan Zhou; Yulei Zhang; Guangli Li; Yu Liao; Changxu Tian (Animals)
Global climate change presents a significant challenge to aquatic ecosystems, with ectothermic fish being particularly sensitive to temperature fluctuations. The brain plays a crucial role in perceiving, regulating, and adapting to thermal changes, and its response to heat stress is crucial for survival. However, the molecular mechanisms underlying heat stress and acclimation in fish brains remain poorly understood. This study aimed to investigate the adaptive mechanisms of Hong Kong catfish (Clarias fuscus) brains under heat acclimation and acute heat stress using transcriptome analysis. Fish were divided into two groups: a normal temperature group (NT, 26 °C for 90 days) and a heat-acclimated group (HT, 34 °C for 90 days), followed by acute heat stress (34 °C for 72 h) and recovery (26 °C for 72 h). Heat acclimation improved C. fuscus tolerance to acute heat stress, with faster gene responses and stronger neuroprotection. Key pathways enriched included cell adhesion and ECM-receptor interactions during recovery. Apoptosis regulation was balanced, with the HT group upregulating anti-apoptotic genes to mitigate neuronal cell death. Additionally, the lysosome–phagosome pathway was activated during recovery, facilitating the transport of lysosomal enzymes and the clearance of damaged cellular components, aiding neuronal repair. Ribosome biogenesis was suppressed under heat stress to conserve energy, but this suppression was less pronounced in the HT group. In summary, heat acclimation enhances neural protection in C. fuscus brains by promoting neuronal repair, suppressing apoptosis, and activating lysosomal pathways, thereby improving tolerance to acute heat stress. These findings offer a molecular basis for breeding heat-tolerant fish species in aquaculture, and deepen our understanding of thermal adaptation in aquatic animals amid global climate change.